Pengaruh Pelatihan Kerja, Motivasi Kerja, dan Reward Kerja terhadap Displin Kerja Karyawan RS Advent - Imelda Surbakti; Ronny Buha Sihotang; Harman Malau (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to review the factors that encourage conscious discipline among employees at the Medan Adventist Hospital. A total of 100 employees as respondents indicated their feelings at work which were assessed through Job Training, Work Motivation, Work Rewards and Work Discipline in their work environment at Medan Adventist Hospital. With an instrument of 35statements that will be answered according to the conditions of each employee. So, through multiple linear regression testing, results were found using the t test of = 3.873 > 1.649 with a significance of 0.00 > 0.05 on job training, so it was stated that Job Training had an effect but not significant on work discipline, t was = 0.828 > 1.649 with a significance of 0.410 > 0.05 on Work Motivation, it is stated that Work Motivation has a significant effect on work discipline, and t = 2.400 > 1.649 with a significance of 0.018 > 0.05 on Work Rewards, then it is stated that Work Rewards has a significant effect on work discipline. Keywords : Job Training, Work Motivation, Work Rewards, Work Discipline